Porous stage assessment of pressure assisted sintering modeling parameters: a ceramic identification method insensitive to final stage grain growth disturbance. (1st June 2021) - Manière, Charles; Harnois, Christelle; Marinel, Sylvain
Abstract: Pressure assisted sintering models such as Skorohod-Olevsky's, Abouaf's or Riedel's require the identification of at least four parameters depending on porosity or temperature. The identification of these parameters is difficult at high temperature and for high pressures because of the non-linear mechanical behavior which makes them closely interconnected. To solve this problem, the fully dense behavior is identified first allowing determining the porous behavior afterward. This typical approach is well employed for metal or viscous materials. However, for ceramics the final stage grain growth makes the fully dense mechanical tests irrelevant; because the equivalent dense phase behavior of sintered specimens has bigger grains (then longer diffusion distances) than in initial/intermediate stages of sintering. Consequently, most of the parameters of these ceramics models compensate the dense parameters overestimation by an underestimation in the porous parameters values. In this paper we propose a unique formulation based on sinter-forging and die compaction which directly identify all the parameters from the porous stage. This comprehensive determination is possible by a non-reductive hypothesis on the shear modulus function shape and the experimental determination of radial/vertical displacement on sinter-forging tests. Such an approach allows an instantaneous determination of the parameters insensitive from the actual grain size of the porous ceramic. Graphical abstract: Image, graphical abstract